CAR: Centro de Artes - Frade, Isabela; Flores de Medeiros , Gilca; Gomes Ramos, Aline Cristina; Campelo Frossard , Rafael; Ramos Brito , Júlia; Valentina Campos , Bernardino; dos Santos Araújo, Giulia; Dias Borges, Carlos Eduardo; de Oliveira Fiel, Arthur Felipe; Henriques , Rafael; Rocha , Camila; D’Abreu , Patrícia; et al. (Guará Journal, 2023)
Resumos de projetos do Centro de Artes